Postoperative Care in Thoracic Surgery : A Comprehensive Guide - Şentürk, Mert; Orhan Sungur, Mukadder (Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive, up-to-date overview of optimal postoperative care in patients who have undergone thoracic surgery and discusses challenging issues that are of interest not only in the context of thoracic surgery but also more generally within the fields of anesthesia, intensive care, and pain medicine. The coverage ranges, for example, from use of non-invasive ventilation, extracorporeal membrane oxygenation, and new monitoring devices to fluid management, pain control, and treatment of arrhythmias. A key feature of the book is the exceptionally attractive list of authors, who represent the most authoritative experts on the topics that they address. The approach is appropriately multidisciplinary, acknowledging that in many centers thoracic anesthetists are responsible for care during the postoperative period. This book is exceptional in being devoted solely to postoperative care in thoracic surgery, even though the difficulties involved in thoracic operations sometimes exceed those of cardiac surgery, especially in the postoperative period.- Resumé vydavatel
Keywords: anestetika; hrudní chirurgie; pooperační péče; anesthetics; chest surgery; postoperative care; elektronické knihy; příručky; electronic books; handbooks and manuals